Cesium-doped tungsten oxide, and preparation method and application thereof

CN122685123BActive Publication Date: 2026-10-30CNNC OPTOELECTRONICS TECH (SHANGHAI) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611185292.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-06
Publication Date
2026-10-30
Estimated Expiration
2046-08-06

AI Technical Summary

Technical Problem

[0006]有鉴于此,本申请提供了一种铯掺杂氧化钨及其制备方法和应用,以解决现有钙钛矿太阳能电池在光利用率、大角度入射光伏性能和纳米光学结构工艺兼容性方面存在的问题

Benefits of technology

[0017]本申请提供了一种铯掺杂氧化钨,具有式(Ⅰ)的化学式:CsxWO3-δ式(Ⅰ);其中,0.01≤δ≤0.5,0.3≤x≤1.2;所述铯掺杂氧化钨为三角形纳米晶;进一步地,在所述铯掺杂氧化钨表面键合功能基团,在纳米结构表面形成有机硅烷功能化层,得到功能化铯掺杂氧化钨。将本申请所述的功能化铯掺杂氧化钨应用于钙钛矿太阳能电池中,通过三种机制协同提升器件性能,第一,通过局域表面等离激元响应(LSPR)效应产生局域光场增强,提高钙钛矿局部光吸收;第二,通过三角构型产生全向散射,延长光程并改善斜入射光吸收;第三,通过表面功能化及其在钙钛矿层中的分布,改善局部电荷分离、传输和提取过程,降低复合损失。实验结果表明,在0°入射角条件下,含功能化铯掺杂氧化钨的钙钛矿太阳能电池具有更高的短路电流密度和光电转换效率,证明LSPR相关局域光场增强和电荷提取增强效应有效;进一步地,在10°~60°入射角条件下,含功能化铯掺杂氧化钨的钙钛矿太阳能电池表现出更小的性能衰减,证明三角构型的功能化铯掺杂氧化钨的全向散射效应能够改善钙钛矿太阳能电池的大角度入射光响应。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122685123B_ABST
    Figure CN122685123B_ABST
Patent Text Reader

Abstract

The application provides a cesium-doped tungsten oxide and a preparation method and application thereof, and relates to the technical field of tungsten compounds. The application provides a cesium-doped tungsten oxide with a chemical formula of formula (I): Cs x WO 3‑δ Formula (I); wherein 0.01≤δ≤0.5, 0.3≤x≤1.2; the cesium-doped tungsten oxide is a triangular nanocrystal. Further, a functional group is bonded to the surface of the cesium-doped tungsten oxide, an organosilane functional layer is formed on the surface of the nanostructure, and functionalized cesium-doped tungsten oxide is obtained. The functionalized cesium-doped tungsten oxide is applied to a perovskite solar cell, and the performance of the device is improved from three mechanisms of localized surface plasmon enhancement, omnidirectional scattering and charge extraction, so that the perovskite solar cell containing the functionalized cesium-doped tungsten oxide is improved in current output, photoelectric conversion efficiency and large-angle incident light response.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of tungsten compound technology, and more particularly to a cesium-doped tungsten oxide, its preparation method, and its application. Background Technology

[0002] Perovskite solar cells represent a significant development direction for next-generation thin-film photovoltaic devices. However, in practical applications, perovskite solar cells still face challenges such as insufficient light absorption efficiency and poor angle adaptability. To address these issues, one approach involves introducing antireflection layers, scattering layers, or light management films onto the device surface or interface to reduce reflection losses and improve light absorption; another approach is to introduce noble metal nanostructures into perovskite solar cells to generate plasmon enhancement.

[0003] While existing antireflection layers and external optical management layers can reduce surface reflection, they suffer from high fabrication costs, complex processes, potential thermal damage or interface disruption to perovskites, and are unfavorable for industrial-scale production. In contrast, plasmonic nanostructures offer an optical enhancement method that can directly affect the electromagnetic field distribution near the light-absorbing layer. The basic principle is that when incident light couples with the collective oscillation of free carriers in the nanostructure, a localized surface plasmonic resonance effect is generated, resulting in an enhanced local electromagnetic field on the nanostructure surface and in the near-field region. For perovskite solar cells, this effect can enhance the local light intensity in the perovskite absorption layer, increase the photogenerated carrier generation rate, and extend the effective propagation path of light in the absorption layer through the scattering effect of the nanostructure. Therefore, plasmonic nanostructures are considered one of the important methods to improve the short-circuit current density, external quantum efficiency, and weak / oblique incident light response of perovskite solar cells.

[0004] Existing plasmon enhancement schemes typically employ Au, Ag, or other irregularly shaped nanostructures, such as nanoparticles, nanorods, nanosheets, or near electrodes, at the interface of the perovskite absorber layer or transport layer. These materials exhibit strong localized surface plasmon response in the visible light range, which can improve the light absorption and photocurrent of perovskite photovoltaic devices to some extent. However, noble metal nanostructures still have significant limitations. First, noble metal materials such as Au and Ag are expensive, hindering the manufacture of low-cost, large-area photovoltaic modules. Second, noble metal nanostructures are prone to introducing interfacial recombination and carrier quenching problems. Third, to achieve plasmon response in the visible light range, noble metal nanostructures usually require large sizes or complex anisotropic morphologies. When large-sized nanostructures are introduced into perovskite films, they can easily interfere with the nucleation and crystallization process of the perovskite precursor solution, leading to uneven grain growth, increased film surface roughness, and an increase in pores or defects, which in turn affects the electrical performance and long-term stability of the device. Fourth, the dispersion stability and process compatibility of noble metal nanostructures are still insufficient. The perovskite antisolvent system is very sensitive to solvent polarity, ligand compatibility, and crystallization kinetics. If conventional noble metal nanoparticles are not specially modified on the surface, they are prone to agglomeration in the antisolvent or to induce uneven crystallization during the perovskite film formation process.

[0005] In summary, while existing noble metal plasmon nanostructures can enhance the local optical field, they suffer from drawbacks such as high cost, interface quenching, large size, and insufficient compatibility with perovskite crystallization and processing. Therefore, there is an urgent need to develop a low-cost, configuration-controllable, optically tunable nanostructure that can be stably dispersed in perovskite antisolvents and directly introduced into the perovskite absorber layer via antisolvent processing. This would improve the light absorption efficiency and large-angle incident light response of perovskite solar cells while minimizing damage to the perovskite crystallization and device interface. Summary of the Invention

[0006] In view of this, this application provides a cesium-doped tungsten oxide, its preparation method and application, to solve the problems existing in perovskite solar cells in terms of light utilization, large-angle incident photovoltaic performance and compatibility with nano-optical structure processes.

[0007] This application provides a cesium-doped tungsten oxide having the chemical formula (I): Cs x WO 3-δ Equation (I); Where, 0.01≤δ≤0.5, 0.3≤x≤1.2; The cesium-doped tungsten oxide is in the form of triangular nanocrystals.

[0008] In some specific implementations, the side length of the triangular nanocrystal is 10nm~20nm.

[0009] This application also provides a functionalized cesium-doped tungsten oxide, comprising the cesium-doped tungsten oxide described in the above technical solution and functional groups bonded to the surface of the cesium-doped tungsten oxide; The functional groups include organosiloxane groups.

[0010] This application also provides a method for preparing cesium-doped tungsten oxide as described in the above technical solution, comprising the following steps: a) Mix the cesium source, organic acid, and first organic phase to obtain the first solution; b) Mix the tungsten source, trioctylphosphine oxygen, and the second organic phase to obtain a second solution; c) React the first solution and the second solution to obtain cesium-doped tungsten oxide.

[0011] In some specific implementations, in step b), the molar ratio of tungsten to trioctylphosphine oxygen in the tungsten source is 1:(0.2~10).

[0012] In some specific implementations, in step c), the molar ratio of cesium in the first solution to tungsten in the second solution is (0.3~1.2):1; The reaction temperature is 260°C to 330°C, and the time is 0.5 min to 60 min.

[0013] This application also provides a perovskite solar cell, comprising: a perovskite absorber layer containing a plasmonic nanostructure; The plasmonic nanostructure is selected from the cesium-doped tungsten oxide described in the above technical solution, the functionalized cesium-doped tungsten oxide described in the above technical solution, or the cesium-doped tungsten oxide prepared by the preparation method described in the above technical solution.

[0014] In some specific implementations, the mass fraction of plasmonic nanostructures in the perovskite absorber layer containing plasmonic nanostructures is 0.01wt%~0.2wt%.

[0015] In some specific implementations, the perovskite solar cell further includes: Base; A first transport layer is formed on the surface of the substrate; the perovskite absorption layer containing plasmon nanostructures is formed on the surface of the first transport layer; A second transport layer is formed on the surface of the perovskite absorber layer containing plasmonic nanostructures; An electrode layer formed on the surface of the second transport layer; The first transport layer and the second transport layer are each independently a hole transport layer and an electron transport layer, and the first transport layer is different from the second transport layer.

[0016] In some specific implementations, the perovskite solar cell further includes: An upper passivation layer is formed between the perovskite absorber layer containing plasmon nanostructures and the second transport layer.

[0017] This application provides a cesium-doped tungsten oxide having the chemical formula of formula (I): Cs x WO 3-δ Formula (I); where 0.01≤δ≤0.5, 0.3≤x≤1.2; the cesium-doped tungsten oxide is triangular nanocrystals; further, functional groups are bonded to the surface of the cesium-doped tungsten oxide to form an organosilanes functionalized layer on the surface of the nanostructure, thus obtaining functionalized cesium-doped tungsten oxide. Applying the functionalized cesium-doped tungsten oxide described in this application to perovskite solar cells, the device performance is synergistically improved through three mechanisms: first, the localized surface plasmon resonance (LSPR) effect enhances the local light field, improving the local light absorption of the perovskite; second, the triangular configuration generates omnidirectional scattering, extending the optical path and improving the absorption of oblique incident light; third, surface functionalization and its distribution in the perovskite layer improve the local charge separation, transport, and extraction processes, reducing recombination losses. Experimental results show that, under 0° incident angle conditions, perovskite solar cells containing functionalized cesium-doped tungsten oxide exhibit higher short-circuit current density and photoelectric conversion efficiency, proving the effectiveness of LSPR-related local light field enhancement and charge extraction enhancement effects. Furthermore, under incident angle conditions of 10°–60°, perovskite solar cells containing functionalized cesium-doped tungsten oxide show smaller performance degradation, demonstrating that the omnidirectional scattering effect of triangularly configured functionalized cesium-doped tungsten oxide can improve the large-angle incident light response of perovskite solar cells. Attached Figure Description

[0018] Figure 1 Cs as described in Embodiment 1 of this application x WO 3-δ Flowchart of the preparation process of -DMOAP nanostructures; Figure 2 Cs as described in Embodiment 1 of this application x WO 3-δ - Transmission electron micrograph of DMOAP. Figure 2 In this application, 'a' refers to Cs as described in Embodiment 1. x WO 3-δ - High-magnification transmission electron microscopy image from DMOAP. Figure 2 b in this application refers to Cs as described in Embodiment 1. x WO 3-δ -Low-magnification transmission electron microscopy image of DMOAP; Figure 3 Cs as described in Embodiment 1 of this application x WO3-δ -DMOAP scattering spectrum and perovskite absorption spectrum; Figure 4 Cs as described in Embodiment 1 of this application x WO 3-δ -Illustrative diagram of omnidirectional scattering of DMOAP and its optical field simulation results in the perovskite absorption layer. Figure 4 In this application, 'a' refers to Cs as described in Embodiment 1. x WO 3-δ -DMOAP omnidirectional scattering diagram Figure 4 b in this application refers to Cs as described in Embodiment 1. x WO 3-δ -DMOAP optical field simulation results in the perovskite absorption layer; Figure 5 Cs as described in Embodiment 1 of this application x WO 3-δ - Schematic diagram of the enhancement mechanism of DMOAP in perovskite solar cells Figure 5 In this application, 'a' refers to Cs as described in Embodiment 1. x WO 3-δ -DMOAP localized surface plasmon effect in perovskite solar cells Figure 5 b in this application refers to Cs as described in Embodiment 1. x WO 3-δ - DMOAP's omnidirectional scattering effect in perovskite solar cells Figure 5 c in this application refers to Cs as described in Embodiment 1 of this application. x WO 3-δ - The charge extraction enhancement effect of DMOAP in perovskite solar cells; Figure 6 For the perovskite solar cells described in Comparative Examples 1 and 2 of this application under different incident angle illumination conditions J - V curve, Figure 6 In Figure 'a', the perovskite solar cell described in Comparative Example 1 of this application is illuminated under different incident angles. J - V curve, Figure 6 In Figure 2, b represents the perovskite solar cell described in Example 2 of this application under different incident angle illumination conditions. J - V curve. Detailed Implementation

[0019] It should be understood that the expression “one or more of…” individually includes each of the objects described after the expression, as well as various different combinations of two or more of the described objects, unless otherwise understood from the context and usage. The expression “and / or” combined with three or more described objects should be understood to have the same meaning, unless otherwise understood from the context.

[0020] The terms “including,” “having,” or “containing,” including the use of their grammatical synonyms, should generally be understood as open-ended and non-restrictive, for example, not excluding other unstated elements or steps, unless otherwise specifically stated or understood from the context.

[0021] It should be understood that the order of steps or the sequence of actions is not important as long as this application remains operational. Furthermore, two or more steps or actions can be performed simultaneously.

[0022] The use of any and all instances or exemplary language such as “e.g.” or “including” herein is merely intended to better illustrate the application and does not constitute a limitation on the scope of the application unless the claims are made. No language in this specification should be construed as indicating that any unclaimed element is essential to the practice of this application.

[0023] Furthermore, the numerical ranges and parameters used to define this application are approximate values, and the relevant values ​​in the specific embodiments have been presented as precisely as possible. However, any value inevitably contains standard deviations due to individual test methods. Therefore, unless otherwise explicitly stated, it should be understood that all ranges, quantities, values, and percentages used in this disclosure are modified with the word "approximately." Here, "approximately" generally means that the actual value is within plus or minus 10%, 5%, 1%, or 0.5% of a specific value or range.

[0024] This application provides a cesium-doped tungsten oxide having the chemical formula (I): Cs x WO 3-δ Equation (I); Where δ represents the degree of oxygen vacancy, 0.01≤δ≤0.5; x represents the amount of Cs doping, 0.3≤x≤1.2; The cesium-doped tungsten oxide is in the form of triangular nanocrystals; Preferably, it has the chemical formula of formula (I): Cs x WO 3-δ Formula (I); where δ represents the degree of oxygen vacancy, 0.01≤δ≤0.5; x represents the Cs doping amount, 0.6≤x≤1.1; the cesium-doped tungsten oxide is triangular nanocrystals; More preferably, it has the chemical formula of formula (I): Cs xWO 3-δ Formula (I); where δ represents the degree of oxygen vacancy, 0.01≤δ≤0.5; x represents the Cs doping amount, 0.8≤x≤1; the cesium-doped tungsten oxide is triangular nanocrystals.

[0025] This application provides a cesium-doped oxygen-vacant tungsten oxide nanostructure, denoted as Cs. x WO 3-δ In this nanostructure, Cs doping and oxygen vacancies jointly regulate the free carrier concentration, enabling it to exhibit localized electromagnetic field enhancement and scattering enhancement in the visible to near-infrared range.

[0026] The Cs x WO 3-δ Nanostructures have a triangular or approximately triangular configuration and exhibit approximately... D 3h Spatial symmetry features. The triangular or near-triangular configuration has multiple sharp corners, multiple edges, and multiple directional crystal planes. This configuration can, on the one hand, form local electromagnetic field concentration in the sharp corner and edge regions, and on the other hand, form multidirectional nano-scattering centers, increasing the propagation path of incident light in the perovskite absorption layer, which is particularly beneficial for improving light absorption under non-perpendicular incident conditions.

[0027] The Cs x WO 3-δ The triangular configuration of the nanostructure can have a side length of 50 nm to 80 nm. By increasing the nucleation rate, shortening the reaction time, increasing the proportion of the structure-directing agent, or rapid quenching, its equivalent size can be controlled to 10 nm to 20 nm. In some specific implementations, the side length of the triangular nanocrystal is 10 nm to 20 nm, preferably 13 nm to 17 nm, and more preferably 14 nm to 16 nm.

[0028] The cesium-doped tungsten oxide described in this application is a non-stoichiometric metal oxide material with tunable free carrier concentration. By adjusting the Cs doping content, oxygen vacancy concentration, crystal structure, and nanoscale size, its localized surface plasmon resonance (LSPR) response and extinction enhancement range can be tuned, enabling its optical response to cover the visible to near-infrared region. Compared to noble metal nanostructures, Cs… x WO 3-δ It possesses advantages such as relatively low raw material costs, good chemical stability, tunable composition and defect states, controllable structural dimensions, and designable configuration. Especially in perovskite-crystalline silicon tandem photovoltaic modules, spectral management needs to consider not only the visible light absorption of the perovskite top cell but also the transmission and utilization of long-wavelength light in the tandem structure. Therefore, Cs with tunable LSPR or extinction response is crucial. x WO 3-δNanostructures can serve as a potential optical management material to improve the light utilization efficiency of perovskite absorption layers and provide a new material basis for spectral modulation in perovskite-crystalline silicon stacked components.

[0029] Besides material composition, the geometry of nanostructures is also a crucial factor determining their optical properties. Different morphologies of nanostructures exhibit different electromagnetic field distributions, polarization responses, and scattering behaviors. For example, spherical particles typically exhibit a more uniform dipole response, while nanostructures with sharp corners, edges, or anisotropic boundaries are more prone to forming electromagnetic field concentrations in localized regions, inducing multidirectional scattering. Therefore, if nanostructures with superior optical performance can be designed proactively, light management efficiency can be improved without significantly increasing material usage. D 3h The spatially symmetrical triangular nanostructures possess both symmetry and anisotropy. Their multiple edges and sharp corners can provide local electromagnetic field enhancement sites, while their multi-directional scattering characteristics facilitate approximate Lambertian scattering behavior, thereby achieving omnidirectional plasmon optical gain. Introducing this type of nanostructure with a special configuration into the perovskite absorber layer is expected to improve the photon utilization and current output of perovskite photovoltaic devices under both perpendicular and large-angle incident conditions.

[0030] This application also provides a method for preparing cesium-doped tungsten oxide as described in the above technical solution, comprising the following steps: a) Mix the cesium source, organic acid, and first organic phase to obtain the first solution; b) Mix the tungsten source, trioctylphosphine oxygen, and the second organic phase to obtain a second solution; c) React the first and second solutions to obtain cesium-doped tungsten oxide.

[0031] This application first mixes a cesium source, an organic acid, and a first organic phase to obtain a first solution. Specifically, the cesium source and the organic acid are dissolved in the first organic phase, degassed under vacuum, and then mixed under an inert atmosphere to obtain the first solution. The first solution is preferably stored at 80°C to 120°C before use to prevent precipitation and facilitate subsequent hot injection.

[0032] The above mixing process takes place in a first organic phase, which is a high-boiling-point organic medium selected from one or both of octadecene and oleylamine, preferably octadecene. In some specific implementations, the molar ratio of cesium to organic acid in the cesium source is 1:(1~5), preferably 1:(1~3). In some specific implementations, the concentration of the first solution is 0.02mol / L~1mol / L, preferably 0.1mol / L~0.3mol / L. In some specific implementations, the cesium source includes, but is not limited to, cesium chloride, cesium carbonate, cesium acetate, or cesium nitrate, and can be one or more of these. When the cesium source is a combination of multiple substances, this application does not have a special limitation on the proportion of each specific substance. In some specific implementations, the cesium source is preferably cesium carbonate. In some specific implementations, the organic acid is selected from C8~C9. 20 Long-chain fatty acids, preferably oleic acid, stearic acid, lauric acid, myristic acid, and palmitic acid, are preferred, with oleic acid being more preferred. In some specific implementations, the degassing treatment is used to remove moisture and oxygen from the system. The degassing treatment temperature is 100°C to 130°C, preferably 115°C to 125°C; the time is 20 min to 60 min, preferably 20 min to 40 min. In some specific implementations, the mixing temperature is 140°C to 180°C, preferably 140°C to 160°C. This application does not have a special limitation on the mixing time; it is preferred to mix until the system forms a clear and transparent solution. In some specific implementations, the inert atmosphere can be argon, nitrogen, or helium, with nitrogen being preferred.

[0033] This application further mixes the tungsten source, trioctylphosphine oxygen, and the second organic phase to obtain a second solution. Specifically, the tungsten source and trioctylphosphine oxygen are dissolved in the second organic phase, degassed under vacuum conditions, and then mixed under an inert atmosphere to obtain the second solution.

[0034] The above mixing process takes place in a second organic phase, which is a high-boiling-point organic medium selected from one or more of oleylamine, oleic acid, octadecene, trioctylphosphine, phenyl ether, and diphenyl ether, preferably oleylamine and oleic acid, and more preferably oleylamine, oleic acid, and octadecene. Oleylamine can act as a high-boiling-point solvent, a weak reducing agent, and a surface ligand, facilitating the formation of Cs. x WO 3-δ Oxygen-deficient structure; oleic acid can regulate the ligand density and particle surface stability of the system. Meanwhile, trioctylphosphine oxide (TOPO), as a structure directing agent, coordinates with the surface of tungsten-oxygen nanocrystals through phospho groups and can selectively adsorb onto high surface energy crystal planes of nanocrystals, such as the {100} crystal plane, thereby inhibiting further growth of the crystal plane and inducing the nanocrystals to grow in a restricted manner along a specific low-energy crystal orientation, ultimately forming triangular or approximately triangular nanostructures.

[0035] In some specific implementations, the molar ratio of tungsten to trioctylphosphine oxygen in the tungsten source is 1:(0.2~10), preferably 1:(1~3). In some specific implementations, the volume ratio of oleylamine, oleic acid, and octadecene is (1~7):1:(2~8), preferably (3~5):1:(4~6). In some specific implementations, the tungsten source includes, but is not limited to, tungsten tetrachloride, tungsten hexacarbonyl, tungsten hexachloride, tungsten chloroform, tungstate, tungstate oleate, or other second organic phase soluble tungsten precursors, and can be one or more of these. When the tungsten source is a combination of multiple substances, this application does not impose any special restrictions on the proportion of each specific substance. In some specific implementations, the tungsten source is preferably tungsten hexacarbonyl. In some specific implementations, the degassing treatment is used to remove moisture and oxygen from the system. The degassing treatment temperature is 80°C~120°C, preferably 90°C~110°C; the time is 20min~60min, preferably 20min~40min. In some specific implementations, the mixing temperature is 260°C to 330°C, preferably 280°C to 310°C, and more preferably 295°C to 305°C. This application does not impose any particular limitation on the mixing time; preferably, mixing is sufficient to form a homogeneous solution. In some specific implementations, the inert atmosphere can be argon, nitrogen, or helium, preferably nitrogen.

[0036] After obtaining the first solution and the second solution, the first solution and the second solution are reacted to obtain cesium-doped tungsten oxide. Specifically, after the temperature of the second solution system stabilizes, the preheated first solution is rapidly injected into the second solution reaction system, and the reaction proceeds after injection to obtain cesium-doped tungsten oxide.

[0037] In some specific implementations, the temperature of the second solution is 260°C to 330°C, preferably 280°C to 310°C, and more preferably 295°C to 305°C. In some specific implementations, the temperature of the first solution is 80°C to 120°C, preferably 90°C to 110°C. In some specific implementations, the rapid injection method is selected from injection pump injection, with an injection rate of 2 mL / min to 8 mL / min, preferably 4 mL / min to 6 mL / min. In some specific implementations, the molar ratio of cesium in the first solution to tungsten in the second solution is (0.3 to 1.2):1, preferably (0.5 to 1.1):1, and more preferably (0.8 to 1):1. In some specific implementations, the reaction temperature is 260°C to 330°C, preferably 280°C to 310°C, more preferably 295°C to 305°C; the time is 0.5 min to 60 min, preferably 1 min to 10 min, more preferably 3 min to 7 min.

[0038] During the reaction, the cesium precursor and the tungsten precursor undergo rapid thermal decomposition, nucleation, and short-term confined growth; TOPO, acting as a structure directing agent, selectively adsorbs onto the high surface energy crystal planes of the nanocrystals, inducing the formation of triangular or approximately triangular Cs. x WO 3-δ Nanostructures.

[0039] After the reaction, the obtained cesium-doped tungsten oxide is further separated and purified. This application does not impose any particular limitation on the method of separation and purification. In some specific implementations, the separation and purification are preferably carried out after the reaction system has cooled to room temperature, by first adding a precipitant, centrifuging to collect the precipitate, and then washing and centrifuging again to obtain cesium-doped tungsten oxide. In some specific implementations, rapid cooling is preferably achieved by air cooling, oil bath transfer, ice-water bath assisted cooling, or adding a low-temperature organic solvent to terminate the continued growth of nanocrystals. In some specific implementations, the precipitant is one or more of ethanol, acetone, ethyl acetate, and isopropanol, preferably ethyl acetate. In some specific implementations, the centrifugation speed is 6000 rpm to 12000 rpm, preferably 8000 rpm to 10000 rpm; the time is 8 min to 15 min, preferably 8 min to 12 min. In some specific implementations, the washing process is preferably performed 2 to 4 times using a toluene / ethanol, chloroform / ethanol, chlorobenzene / ethanol, or hexane / ethanol mixed solvent, preferably 3 times using a toluene / ethanol mixed solvent, to remove unreacted precursors, free TOPO, oleic acid, and oleylamine.

[0040] The method for preparing cesium-doped tungsten oxide described in this application aims to prepare triangular or approximately triangular Cs oxides via a trioctylphosphine oxygen structure-directed hot-injection method. x WO 3-δ Nanostructures were developed, and their size, configuration, oxygen vacancy concentration, and plasmon enhancement sites were controlled by adjusting the TOPO / W molar ratio, oleylamine / oleic acid ratio, cesium / tungsten feed ratio, reaction temperature, reaction time, injection rate, cooling method, and amount of structure-directing agent.

[0041] This application also provides a functionalized cesium-doped tungsten oxide, comprising cesium-doped tungsten oxide and functional groups bonded to the surface of the cesium-doped tungsten oxide; the functional groups include organosiloxane groups.

[0042] The functionalized cesium-doped tungsten oxide includes cesium-doped tungsten oxide (Cs). x WO 3-δ The cesium-doped tungsten oxide described above will not be repeated here.

[0043] The functionalized cesium-doped tungsten oxide includes functional groups bonded to the surface of the cesium-doped tungsten oxide; the functional groups include organosiloxane groups. In some specific implementations, the organosiloxane groups include, but are not limited to, trimethoxysilyl groups or triethoxysilyl groups.

[0044] This application relates to the aforementioned Cs. x WO 3-δ Further surface functionalization yielded functionalized cesium-doped tungsten oxide, enhancing Cs x WO 3-δ Compatibility, dispersion stability and anti-agglomeration ability in perovskite antisolvents.

[0045] This application also provides a method for preparing functionalized cesium-doped tungsten oxide, comprising the following steps: a) Mix the cesium source, organic acid, and first organic phase to obtain the first solution; b) Mix the tungsten source, trioctylphosphine oxygen, and the second organic phase to obtain a second solution; c) React the first and second solutions to obtain cesium-doped tungsten oxide; d) React cesium-doped tungsten oxide with an organosilanes coupling agent to obtain functionalized cesium-doped tungsten oxide.

[0046] The preparation method of cesium-doped tungsten oxide described in this application is as described above, and will not be repeated here.

[0047] Functionalized cesium-doped tungsten oxide is obtained by reacting cesium-doped tungsten oxide with an organosilane coupling agent. Specifically, cesium-doped tungsten oxide is dispersed in a solvent, and an organosilane coupling agent is added to react and obtain functionalized cesium-doped tungsten oxide.

[0048] The above reaction is preferably carried out with trace amounts of water and a weakly acidic or weakly basic catalyst to create a weakly acidic or weakly basic environment. In some specific implementations, the volume of water is 50 μL to 100 μL, preferably 70 μL to 90 μL; the weakly acidic catalyst is acetic acid, preferably with a volume of 15 μL to 25 μL. In some specific implementations, the solvent is one or more of toluene, chloroform, ethanol, and isopropanol, preferably toluene and ethanol; the volume ratio of toluene to ethanol is (1~4):1, preferably (1~3):1. In some specific implementations, the mass ratio of cesium-doped tungsten oxide to organosilanes is 1:(0.05~5), preferably 1:(0.2~2). In some specific implementations, the reaction temperature is 30℃ to 90℃, preferably 50℃ to 80℃, more preferably 50℃ to 70℃; the reaction time is 1h to 24h, preferably 4h to 12h, more preferably 9h to 11h. In some specific implementations, the organosilane coupling agent includes, but is not limited to, dimethyloctadecyl[3-trimethoxysilylpropyl]ammonium chloride, dodecyltrimethoxysilane, octadecyltrimethoxysilane, octyltrimethoxysilane, or aminopropyltriethoxysilane, and may be one or more of these. When the organosilane coupling agent is a combination of multiple substances, this application does not impose any special restrictions on the proportion of each specific substance. In some specific implementations, the organosilane coupling agent is preferably dimethyloctadecyl[3-trimethoxysilylpropyl]ammonium chloride (DMOAP).

[0049] After the reaction is complete, the product is preferably precipitated by adding ethanol, ethyl acetate, acetone or isopropanol, preferably ethyl acetate, and unreacted organosilane coupling agent and free ligand are removed by centrifugation and washing.

[0050] In some specific implementations, a typical process for functionalizing cesium-doped tungsten oxide using DMOAP is as follows: The trimethoxysilyl group in the DMOAP molecule undergoes hydrolysis to form a silanol intermediate, which then reacts with Cs. x WO 3-δ Condensation reactions occur at hydroxyl groups, oxygen vacancies, or metal-oxygen bond sites on the surface, forming an organosilanes functionalized layer on the nanostructure surface. The DMOAP molecule contains a trimethoxysilyl group, a quaternary ammonium salt group, and an octadecyl long chain. The trimethoxysilyl group can hydrolyze in the presence of trace amounts of water to form silanol groups, which then react with Cs... x WO 3-δ The hydroxyl groups, metal oxygen bond sites, or oxygen vacancy sites on the surface undergo condensation reactions to form WO-Si bonds or surface siloxane networks; the octadecyl long chain is used to improve the compatibility of the nanostructure with organic antisolvents; the quaternary ammonium salt groups can improve the surface stability and anti-agglomeration ability of the particles.

[0051] The method for preparing functionalized cesium-doped tungsten oxide described in this application aims to enhance the performance of Cs by using DMOAP or other long-chain organosilane coupling agents. x WO 3-δ Surface functionalization is performed to make it stably dispersed in perovskite antisolvents such as chlorobenzene, ethyl acetate, toluene, and isopropanol.

[0052] This application also provides a perovskite solar cell, comprising: a perovskite absorber layer containing a plasmonic nanostructure; wherein the plasmonic nanostructure is cesium-doped tungsten oxide as described in the above technical solution, functionalized cesium-doped tungsten oxide as described in the above technical solution, or cesium-doped tungsten oxide prepared by the preparation method of cesium-doped tungsten oxide as described in the above technical solution.

[0053] The perovskite solar cell includes a perovskite absorber layer containing plasmonic nanostructures. In some specific implementations, the mass fraction of plasmonic nanostructures in the perovskite absorber layer is 0.01wt%~0.2wt%, preferably 0.02wt%~0.15wt%, and more preferably 0.05wt%~0.10wt%.

[0054] The enhancement mechanism of functionalized cesium-doped tungsten oxide nanotriangles in perovskite solar cells described in this application includes localized surface plasmon resonance (LSPR), omnidirectional scattering, and charge extraction enhancement.

[0055] First, Cs x WO 3-δ Cs doping and oxygen vacancies in Cs can tune the free carrier concentration, leading to localized surface plasmon-related optical enhancement effects. x WO 3-δ When distributed within the perovskite absorption layer, it can form an enhanced local optical field around the nanostructure, thereby improving the local light absorption and photogenerated carrier generation rate of the perovskite.

[0056] Second, the triangular configuration Cs x WO 3-δ With its edges, sharp corners, and multi-directional geometric boundaries, it can induce omnidirectional scattering of incident light. This scattering effect can extend the effective propagation path of light in the perovskite absorption layer, which is particularly beneficial for improving the absorption capacity of the device under non-perpendicular incident light conditions.

[0057] Third, Cs after surface functionalization x WO 3-δ Nanotriangles can be well dispersed in the perovskite absorber layer, and their Poynting vectors can cover the transport layer region. They may improve the carrier separation, transport and extraction process in local areas, reduce local recombination loss, and thus promote charge extraction.

[0058] The three effects mentioned above work together to enhance the functionality of Cs. x WO 3-δ The perovskite devices have been improved in terms of current output, photoelectric conversion efficiency and response to large-angle incident light.

[0059] In some specific implementations, a typical structure of the perovskite solar cell includes: Base; A first transport layer is formed on the surface of the substrate; A perovskite absorber layer containing plasmonic nanostructures is formed on the surface of the first transport layer; A second transport layer is formed on the surface of the perovskite absorber layer containing plasmonic nanostructures; An electrode layer formed on the surface of the second transport layer; The first transport layer and the second transport layer are each independently a hole transport layer and an electron transport layer, and the first transport layer is different from the second transport layer.

[0060] When a perovskite solar cell is inverted (pin) structure, in some specific implementations, the hole transport layer is located between the substrate and the perovskite absorber layer containing plasmon nanostructures, and the electron transport layer is located between the perovskite absorber layer containing plasmon nanostructures and the electrode layer. In this case, a typical perovskite solar cell structure, from bottom to top, includes: a substrate, a hole transport layer, a perovskite absorber layer containing plasmon nanostructures, an electron transport layer, and an electrode layer. When a perovskite solar cell is nip structure, in some specific implementations, the electron transport layer is located between the substrate and the perovskite absorber layer containing plasmon nanostructures, and the hole transport layer is located between the perovskite absorber layer containing plasmon nanostructures and the electrode layer. In this case, a typical perovskite solar module structure, from bottom to top, includes: a substrate, an electron transport layer, a perovskite absorber layer containing plasmon nanostructures, a hole transport layer, and an electrode layer.

[0061] The perovskite solar cell includes a substrate. The substrate collects and transports photogenerated carriers and provides mechanical support for the device. In some specific implementations, the substrate is an indium tin oxide (ITO) glass substrate or a fluorine-doped tin oxide (FTO) glass substrate, preferably an ITO glass substrate. In some specific implementations, the film thickness of the substrate is 120 nm to 200 nm, preferably 140 nm to 160 nm, and more preferably 145 nm to 155 nm.

[0062] The perovskite solar cell includes a hole transport layer. This hole transport layer efficiently transports holes to the electrodes while blocking electrons from moving to the outer electrodes, thus achieving carrier separation. In some specific implementations, the material of the hole transport layer is selected from one or more of nickel oxide, [2-(9,9-dimethyl-9H-fluoren-2-yl)ethyl]phosphonic acid (2PACz), (4-(3,6-dimethoxy-9H-carbazole-9-yl)butylphosphonic acid) (MeO-4PACz), (4-(9H-carbazole-9-yl)butylphosphonic acid) (4PACz), and (2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl)phosphonic acid (MeO-2PACz).

[0063] In some specific implementations, the hole transport layer preferably includes a main hole transport layer and an interface modification layer formed on the surface of the main hole transport layer. The main hole transport layer of this application is used to provide a hole-selective transport channel and improve the interface energy level matching between the substrate and the perovskite absorber layer containing plasmon nanostructures. In some specific implementations, the material of the main hole transport layer is preferably nickel oxide, with a thickness of 10nm~20nm, preferably 15nm~19nm, and more preferably 16nm~18nm. The interface modification layer of this application is used to further improve hole-selective contact, reduce interfacial recombination, and improve the film quality of the perovskite absorber layer on the substrate. In some specific implementations, the material of the interface modification layer is preferably (2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl)phosphonic acid (MeO-2PACz), with a thickness of 1nm~5nm, preferably 1nm~3nm, and more preferably 1.5nm~2.5nm. In some specific implementations, the hole transport layer is preferably NiO. X / MeO-2PACz.

[0064] The perovskite solar cell includes a perovskite absorber layer containing plasmonic nanostructures. The perovskite absorber layer containing plasmonic nanostructures comprises a perovskite absorber layer and plasmonic nanostructures distributed within the perovskite absorber layer, near grain boundaries, or on the surface of the thin film. The purpose of the plasmonic nanostructures in the perovskite absorber layer is as described above and will not be repeated here. The pure perovskite absorber layer is the core component of the perovskite solar cell module, used to absorb sunlight and excite electrons and holes.

[0065] In some specific implementations, the selection of the plasmonic nanostructure is as described above, and will not be repeated here. In some specific implementations, the material of the perovskite absorber layer has the atomic ratio shown in Formula (II): ABX3 (Formula (II)), where A includes, but is not limited to, formamidinium ions (FA). + ), Methylamine ion (MA +), cesium ions (Cs) + ) or rubidium ions (Rb + The ions A can be one or more of these ions. When A is a variety of ions, this application does not impose any special restrictions on the specific proportions of each ion. In some specific implementations, A is preferably a formamidinium ion (FA). + ), Methylamine ion (MA + ) and cesium ions (Cs + B includes, but is not limited to, lead ions (Pb). 2+ ), tin ions (Sn) 2+ or germanium ions (Ge 2+ The ions B can be one or more of these, and when B is a variety of ions, this application does not impose any special restrictions on the specific proportions of each ion. In some specific implementations, the B is preferably lead ion (Pb). 2+ X is a halide ion, which can be an iodide ion (I). - ), bromide ions (Br) - ) or chloride ions (Cl - X can be one or more of these ions, and when X is a variety of ions, this application does not impose any special restrictions on the specific proportions of each ion. In some specific implementations, X is preferably an iodide ion (I... - ) and bromide ions (Br - In some specific implementations, the perovskite active layer material preferably has the atomic ratio shown in formula (II): Cs x (MA y FA 1-y ) 1-x Pb(I u Br 1-u )3(Ⅲ), where 0≤x≤1, 0≤y≤1, 0≤u≤1, more preferably Cs 0.05 (MA 0.10 FA 0.90 ) 0.95 Pb(I 0.90 Br 0.10 3.

[0066] The concentration of the plasmonic nanostructures described in this application can be controlled according to the device performance. When the concentration is too low, the local plasmonic enhancement and scattering enhancement effects are insufficient; when the concentration is too high, it may cause nanostructure aggregation and an increase in perovskite crystal defects. In some specific implementations, the mass fraction of the plasmonic nanostructures in the perovskite absorber layer containing the plasmonic nanostructures is 0.01wt%~0.2wt%, preferably 0.02wt%~0.15wt%, and more preferably 0.05wt%~0.10wt%. In some specific implementations, the thickness of the perovskite absorber layer containing the plasmonic nanostructures is 200nm~500nm, preferably 250nm~350nm, and more preferably 290nm~310nm.

[0067] The perovskite solar cell includes an electron transport layer. This electron transport layer efficiently transports electrons to the electrodes and blocks holes from moving to the outer electrodes, thus separating charge carriers and preventing direct contact between the perovskite layer and the electrodes, which could lead to internal short circuits.

[0068] In some specific implementations, the electron transport layer includes a main electron transport layer and a buffer layer formed on the surface of the main electron transport layer. In some specific implementations, the material of the main electron transport layer is selected from fullerene C. 60 SnO2, TiO2, [6,6]-phenyl-C 61 Isomethyl butyrate (PC) 61 BM) and [6,6]-phenyl-C 71 One or more of isomethyl butyrate, preferably [6,6]-phenyl-C 61 Isomethyl butyrate (PC) 61 The buffer layer (BM) has a thickness of 15nm to 25nm, preferably 18nm to 22nm. In some specific implementations, the material of the buffer layer is selected from copper bath (BCP) or lithium fluoride (LiF), preferably copper bath (BCP), and the thickness is 3nm to 8nm, preferably 4nm to 6nm. In some specific implementations, the electron transport layer is preferably PC. 61 BM / BCP.

[0069] The perovskite solar cell includes an electrode layer. The electrode layer collects photogenerated carriers and leads them to an external circuit. In some specific implementations, the material of the electrode layer is selected from metal electrodes, carbon-based electrodes, or transparent bottom electrodes, preferably metal electrodes. In some specific implementations, the metal back electrode is preferably an Ag electrode. In some specific implementations, the thickness of the electrode layer is 50 nm to 150 nm, preferably 70 nm to 130 nm, and more preferably 90 nm to 110 nm.

[0070] In some specific implementations, the perovskite solar cell further includes: An upper passivation layer is formed between the perovskite absorber layer containing plasmon nanostructures and the second transport layer.

[0071] In some specific implementations, the material of the upper passivation layer is selected from organic ammonium salts or diammonium salts, preferably one or more of phenylethyl ammonium iodide (PEAI), 2-(4-fluorophenyl)ethyl ammonium iodide (FPEAI), n-octyl ammonium iodide (OAI), butyl ammonium iodide (BAI), 1,3-propanediamine dihydroiodide (PDAI2), ethylenediamine dihydroiodide (EDAI2), and 1,4-butanediamine dihydroiodide (BDAI2), more preferably 1,4-butanediamine iodide (BDAI2). In some specific implementations, the thickness of the upper passivation layer is 2 nm to 10 nm, preferably 3 nm to 8 nm, more preferably 4 nm to 6 nm.

[0072] This application also provides a method for fabricating a perovskite solar cell, comprising the following steps: A first transport layer is formed on the substrate surface; A perovskite absorption layer containing plasmonic nanostructures is formed on the surface of the first transport layer; A second transport layer is formed on the surface of the perovskite thin film; An electrode layer is formed on the surface of the second transport layer; The first transport layer and the second transport layer are each independently a hole transport layer and an electron transport layer, and the first transport layer is different from the second transport layer.

[0073] In some specific implementations, when the perovskite solar cell has a normal structure (nip), the first transport layer is an electron transport layer and the second transport layer is a hole transport layer. In some specific implementations, when the perovskite solar cell has an inverted structure (pin), the first transport layer is a hole transport layer and the second transport layer is an electron transport layer.

[0074] When the perovskite solar cell is of an inverted (pin) structure, the method for fabricating the perovskite solar cell includes the following steps: A hole transport layer is formed on the substrate surface; A perovskite absorption layer containing plasmonic nanostructures is formed on the surface of the hole transport layer; An electron transport layer is formed on the surface of the perovskite thin film; An electrode layer is formed on the surface of the electron transport layer.

[0075] This application first forms a hole transport layer on the substrate surface. Specifically, the substrate is cleaned and pretreated, and the hole transport layer is formed on the cleaned and pretreated substrate surface.

[0076] The selection of the substrate and the thickness of the film layer on the substrate have been described above, and will not be repeated here. In some specific implementations, the cleaning is preferably performed by ultrasonic cleaning in sequence with a cleaning agent, deionized water, acetone, and isopropanol, and finally dried with a nitrogen air gun. In some specific implementations, the ultrasonic cleaning time in the cleaning agent, deionized water, acetone, and isopropanol is independently 10 min to 30 min, preferably 15 min to 25 min. In some specific implementations, the pretreatment is to subject the cleaned substrate to ultraviolet ozone treatment for 5 min to 20 min, preferably 10 min to 20 min, to remove surface organic residues and improve surface wettability.

[0077] A hole transport layer is formed on the surface of the substrate after cleaning and pretreatment. Specifically, a hole transport layer material solution is spin-coated onto the surface of the substrate after cleaning and pretreatment, and then annealed to form the hole transport layer. Further, preferably, a main hole transport layer material solution is first spin-coated onto the surface of the substrate after cleaning and pretreatment to form the main hole transport layer; then, an interface modification layer material solution is spin-coated onto the surface of the main hole transport layer, and finally, after annealing, the hole transport layer is formed.

[0078] The material selection and thickness of the main hole transport layer and the interface modification layer have been described above and will not be repeated here. In some specific implementations, the solvent of the material solution for the main hole transport layer is preferably water, with a concentration of 10 mg / mL to 30 mg / mL, preferably 15 mg / mL to 25 mg / mL. In some specific implementations, when forming the main hole transport layer, the spin coating speed is 1000 rpm to 5000 rpm, preferably 2000 rpm to 4000 rpm; the time is 10 s to 50 s, preferably 20 s to 40 s. In some specific implementations, the solvent of the material solution for the interface modification layer is preferably ethanol, with a concentration of 0.2 mg / mL to 0.8 mg / mL, preferably 0.4 mg / mL to 0.6 mg / mL. In some specific implementations, when forming the interface modification layer, the spin coating speed is 2000 rpm to 6000 rpm, preferably 3000 rpm to 5000 rpm; the time is 10 s to 50 s, preferably 20 s to 40 s. In some specific implementations, the annealing temperature is 80℃ to 120℃, preferably 90℃ to 110℃, and the time is 5 min to 20 min, preferably 5 min to 15 min.

[0079] After the hole transport layer is formed, a perovskite absorber layer containing plasmonic nanostructures is formed on the surface of the hole transport layer. Specifically, the sample is transferred to a nitrogen glove box, and a perovskite precursor solution is spin-coated onto the surface of the hole transport layer to form a perovskite wet film. During the formation of the perovskite wet film, an antisolvent dispersion containing plasmonic nanostructures is drop-added to the surface. After annealing, a perovskite absorber layer containing plasmonic nanostructures is formed.

[0080] This application controls the proportion of each ion in the perovskite active layer by controlling the molar ratio of A, B, and X, thereby preparing a perovskite precursor solution. The selection of the perovskite material is as described above and will not be repeated here. In some specific implementations, the concentration of the perovskite precursor solution is 0.5 mol / L to 2.5 mol / L, preferably 1 mol / L to 2 mol / L, and the volume is 40 μL to 70 μL, preferably 45 μL to 55 μL. In some specific implementations, the solvent of the perovskite precursor solution is a mixed solvent, selected from at least two of N,N-dimethylformamide, dimethyl sulfoxide, and N-methylpyrrolidone, preferably N,N-dimethylformamide and dimethyl sulfoxide. This application does not have any special limitation on the proportion of the above mixed solvent. In some specific implementations, the volume ratio of N,N-dimethylformamide to dimethyl sulfoxide is preferably 2 to 6:1, more preferably 3 to 5:1. In some specific implementations, the spin coating speed of the perovskite precursor solution is 4000 rpm to 8000 rpm, preferably 5000 rpm to 7000 rpm; the time is 30 s to 60 s, preferably 40 s to 50 s.

[0081] The antisolvent dispersion described in this application includes an organic antisolvent and plasmonic nanostructures dispersed therein; the selection of the plasmonic nanostructures is as described above and will not be repeated here. In some specific implementations, the concentration of the plasmonic nanostructures in the antisolvent dispersion is 0.001 mg / mL to 10 mg / mL, preferably 0.05 mg / mL to 0.5 mg / mL, more preferably 0.2 mg / mL to 0.3 mg / mL; the volume is 50 μL to 200 μL, preferably 100 μL to 200 μL, more preferably 140 μL to 160 μL. In some specific implementations, the organic antisolvent is one or more of chlorobenzene, ethyl acetate, toluene, isopropanol, chloroform, anisole, and diethyl ether, preferably chlorobenzene, ethyl acetate, toluene, or isopropanol, more preferably ethyl acetate. In some specific implementations, the antisolvent dispersion preferably shows no significant sedimentation after standing at room temperature for 24 hours, or can recover a uniform dispersion state after short-term sonication. In some specific implementations, preferably, an antisolvent dispersion containing plasmon nanostructures is added dropwise 15 to 25 seconds after the start of spin coating of the perovskite precursor solution to induce rapid nucleation and crystallization of the perovskite. In some specific implementations, the annealing temperature is 80°C to 120°C, preferably 90°C to 110°C, and the time is 5 min to 25 min, preferably 10 min to 20 min.

[0082] In this application, the perovskite absorber layer containing plasmonic nanostructures is prepared using an antisolvent method. The plasmonic nanostructures are not introduced as an independent interface layer or external scattering layer, but rather directly incorporated into the perovskite absorber layer via an antisolvent drop-addition process. In this way, the plasmonic nanostructures enter the perovskite wet film during the antisolvent-induced crystallization process and remain within the perovskite absorber layer, near grain boundaries, or on the film surface during subsequent annealing. This method enables in-situ distribution of nano-optical enhancement structures within the perovskite film or near grain boundaries without significantly altering the original perovskite device fabrication process.

[0083] After forming a perovskite absorber layer containing plasmonic nanostructures, an electron transport layer is formed on the surface of the perovskite film. Specifically, an electron transport layer material solution is spin-coated onto the surface of the perovskite absorber layer containing plasmonic nanostructures, and then annealed to form the electron transport layer. Further, preferably, a main electron transport layer material solution is first spin-coated onto the surface of the perovskite absorber layer containing plasmonic nanostructures to form the main electron transport layer; then, a buffer layer material solution is spin-coated onto the surface of the main electron transport layer to form the electron transport layer.

[0084] The material selection and thickness of the main electron transport layer and the buffer layer have been described above and will not be repeated here. In some specific implementations, the solvent of the material solution for the main electron transport layer is preferably chlorobenzene, with a concentration of 10 mg / mL to 30 mg / mL, preferably 15 mg / mL to 25 mg / mL. In some specific implementations, when forming the main electron transport layer, the spin coating speed is 1000 rpm to 2500 rpm, preferably 1500 rpm to 2000 rpm; the time is 10 s to 50 s, preferably 20 s to 40 s. In some specific implementations, the solvent of the material solution for the buffer layer is preferably isopropanol, with a concentration of 0.2 mg / mL to 0.8 mg / mL, preferably 0.4 mg / mL to 0.6 mg / mL. In some specific implementations, when forming the buffer layer, the spin coating speed is 4000rpm~8000rpm, preferably 5000rpm~7000rpm; the time is 10s~50s, preferably 20s~40s.

[0085] After the electron transport layer is formed, an electrode layer is formed on the surface of the electron transport layer. The material selection and thickness of the electrode layer are as described above, and will not be repeated here. This application does not impose any special restrictions on the preparation method of the back electrode layer. In some specific implementations, the electrode layer is preferably prepared by vacuum thermal evaporation deposition.

[0086] Furthermore, in some specific implementations, the method for fabricating the perovskite solar cell includes the following steps: A hole transport layer is formed on the substrate surface; A perovskite absorption layer containing plasmonic nanostructures is formed on the surface of the hole transport layer; An upper passivation layer is formed on the surface of the perovskite absorber layer containing plasmon nanostructures; An electron transport layer is formed on the surface of the upper passivation layer; An electrode layer is formed on the surface of the electron transport layer.

[0087] The fabrication of the substrate, hole transport layer, perovskite thin film, and electron transport layer has been described above and will not be repeated here.

[0088] The method for preparing the upper passivation layer includes the following steps: A material solution with a passivation layer spin-coated onto the surface of the perovskite absorber layer containing plasmon nanostructures is annealed to form an upper passivation layer.

[0089] The upper passivation layer can reduce the defect density on the perovskite surface and improve the interfacial contact between the perovskite and the subsequent electron transport layer. The material selection and thickness of the upper passivation layer are as described above and will not be repeated here. In some specific implementations, the solvent of the material solution for the upper passivation layer is preferably a mixed solvent of isopropanol and dimethyl sulfoxide (IPA / DMSO), with a volume ratio of isopropanol to dimethyl sulfoxide of 100~500:1, preferably 150~250:1. In some specific implementations, the concentration of the material solution for the upper passivation layer is 0.5mg / mL~2mg / mL, preferably 0.5mg / mL~1.5mg / mL. In some specific implementations, the spin coating speed is 1000rpm~2500rpm, preferably 1500rpm~2000rpm; the time is 10s~50s, preferably 20s~40s. In some specific implementations, the annealing temperature is 80℃~120℃, preferably 90℃~110℃, and the time is 1min~10min, preferably 4min~6min.

[0090] When the perovskite solar cell is a formal structure (nip), the fabrication method of the perovskite solar cell includes the following steps: An electron transport layer is formed on the substrate surface; A perovskite absorption layer containing plasmonic nanostructures is formed on the surface of the electron transport layer; A hole transport layer is formed on the surface of the perovskite thin film; An electrode layer is formed on the surface of the hole transport layer.

[0091] Furthermore, in some specific implementations, the method for fabricating the perovskite solar cell includes the following steps: An electron transport layer is formed on the substrate surface; A perovskite absorption layer containing plasmonic nanostructures is formed on the surface of the electron transport layer; An upper passivation layer is formed on the surface of the perovskite absorber layer containing plasmon nanostructures; A hole transport layer is formed on the surface of the upper passivation layer; An electrode layer is formed on the surface of the hole transport layer.

[0092] The fabrication of the substrate, electron transport layer, perovskite thin film, upper passivation layer and electron transport layer are as described above, and will not be repeated here.

[0093] This application first provides a cesium-doped tungsten oxide having the chemical formula of formula (I): Cs x WO 3-δFormula (I); where 0.01≤δ≤0.5, 0.3≤x≤1.2; the cesium-doped tungsten oxide is triangular nanocrystals; further, functional groups are bonded to the surface of the cesium-doped tungsten oxide to form an organosilanes functionalized layer on the surface of the nanostructure, thus obtaining functionalized cesium-doped tungsten oxide. Applying the functionalized cesium-doped tungsten oxide described in this application to perovskite solar cells, the device performance is synergistically improved through three mechanisms: first, the localized surface plasmon resonance (LSPR) effect enhances the local light field, improving the local light absorption of the perovskite; second, the triangular configuration generates omnidirectional scattering, extending the optical path and improving the absorption of oblique incident light; third, surface functionalization and its distribution in the perovskite layer improve the local charge separation, transport, and extraction processes, reducing recombination losses. Experimental results show that, under 0° incident angle conditions, perovskite solar cells containing functionalized cesium-doped tungsten oxide exhibit higher short-circuit current density and photoelectric conversion efficiency, proving the effectiveness of LSPR-related local light field enhancement and charge extraction enhancement effects. Furthermore, under incident angle conditions of 10°–60°, perovskite solar cells containing functionalized cesium-doped tungsten oxide show smaller performance degradation, demonstrating that the omnidirectional scattering effect of triangularly configured functionalized cesium-doped tungsten oxide can improve the large-angle incident light response of perovskite solar cells.

[0094] The present invention is further illustrated below with reference to the embodiments. The scope of protection of the present invention is not limited to the following embodiments.

[0095] Example 1

[0096] This embodiment provides a DMOAP-functionalized triangle Cs x WO 3-δ (Cs) x WO 3-δ The preparation method and process for the -DMOAP nanostructure are described in [reference]. Figure 1 The specific steps are as follows: 1. Preparation of cesium oleate precursor: 0.6516 g of cesium carbonate, 3.2 mL of oleic acid, and 16.8 mL of octadecene were added to a three-necked flask and stirred under nitrogen protection. First, the mixture was degassed under vacuum at 120 °C for 30 min to remove moisture and oxygen. Then, nitrogen protection was switched, and the temperature was raised to 150 °C until a clear, transparent solution was formed, yielding a cesium oleate precursor solution with a cesium concentration of approximately 0.20 mol / L. This cesium oleate precursor solution was stored at 80 °C–120 °C before use.

[0097] 2. Construction of the tungsten precursor-TOPO reaction system: Add 0.3519 g of tungsten hexacarbonyl, 0.773 g of trioctylphosphine oxide, 8 mL of oleylamine, 2 mL of oleic acid, and 10 mL of octadecene to another three-necked flask. The amount of tungsten hexacarbonyl is 1 mmol, and the amount of trioctylphosphine oxide is approximately 2 mmol, i.e., the TOPO / W molar ratio is approximately 2:1.

[0098] The above mixture was degassed under vacuum at 100°C for 30 minutes to remove moisture and oxygen. Then, nitrogen protection was switched on and the temperature was raised to 300°C to form a homogeneous tungsten precursor-TOPO reaction system.

[0099] 3. Preparation of triangular Cs by hot injection reaction x WO 3-δ : Once the temperature of the tungsten precursor-TOPO reaction system stabilized at 300℃, the preheated 100℃ cesium oleate precursor solution was rapidly injected into the tungsten precursor-TOPO system. To achieve a theoretical Cs / W molar ratio of 0.9, 4.5 mL of a 0.20 mol / L cesium oleate precursor solution was injected into the precursor system containing 1 mmol of tungsten, corresponding to a theoretical molar amount of Cs of 0.9 mmol. The injection was performed using a syringe pump at a rate of 5 mL / min.

[0100] After injection, the reaction was continued at 300°C for 5 minutes. After the reaction was completed, the heating source was immediately removed, and the temperature was rapidly reduced by transferring the nanocrystals in an oil bath to stop further growth.

[0101] 4. Triangle Cs x WO 3-δ Separation and purification: After the reaction system has cooled to room temperature, 50 mL of ethyl acetate is added to the reaction solution as a precipitant to allow Cs to precipitate. x WO 3-δ It precipitates from the reaction system.

[0102] The precipitate was then centrifuged at 9500 rpm for 10 min and collected. The precipitate was washed three times with a toluene / ethanol mixture to remove unreacted precursors, free TOPO, oleic acid, and oleylamine. Finally, the precipitate was redispersed in 20 mL of a toluene / ethanol mixture (toluene to ethanol volume ratio 2:1) to obtain the initial triangular Cs... x WO 3-δ Dispersion.

[0103] 5. Triangle Cs x WO 3-δ Functionalization of DMOAP surfaces: To the above initial triangle Cs x WO 3-δ0.8 mL of DMOAP solution was added to the dispersion, along with 80 μL of deionized water and 20 μL of acetic acid, to create a weakly acidic environment. The mixture was then stirred at 60°C for 10 h.

[0104] After the reaction was complete, the system was cooled to room temperature, and the product was precipitated by adding ethyl acetate and centrifuged at 9500 rpm for 10 min. The resulting precipitate was washed and redispersed in ethyl acetate to obtain DMOAP-functionalized Cs. x WO 3-δ (Cs) x WO 3-δ ethyl acetate antisolvent dispersion of -DMOAP, Cs x WO 3-δ The concentration of -DMOAP in ethyl acetate is 0.25 mg / mL.

[0105] Example 2

[0106] DMOAP-functionalized Cs prepared in Example 1 was introduced onto the surface of the perovskite absorber layer of a perovskite solar cell. x WO 3-δ (Cs) x WO 3-δ -DMOAP) nanostructure, the device structure is: ITO / NiO X / MeO-2PACz / Cs x WO 3-δ -DMOAP-modified perovskite absorber layer / top passivation layer / PC 61 BM / BCP / Ag.

[0107] 1. ITO substrate cleaning and pretreatment: The ITO glass substrate was ultrasonically cleaned sequentially in a cleaning agent, deionized water, acetone, and isopropanol for 20 minutes each. The ITO film thickness on the ITO glass substrate was 150 nm. After cleaning, the substrate surface was dried with nitrogen gas. Subsequently, the cleaned ITO substrate was subjected to ultraviolet ozone treatment for 15 minutes to remove organic residues and improve surface wettability.

[0108] 2. NiO X Fabrication of the hole transport layer: NiO with a concentration of 20 mg / mL X Aqueous dispersions of nanoparticles were spin-coated onto an ITO substrate at 3000 rpm for 30 seconds to form NiO. X Hole transport layer, with a thickness of 17nm.

[0109] 3. Preparation of MeO-2PACz self-assembled molecular layers: A 0.5 mg / mL MeO-2PACz ethanol solution was spin-coated onto NiO. X The surface of the layer was spin-coated at 4000 rpm for 30 seconds. After spin-coating, the sample was annealed at 100°C for 10 minutes to form NiO. X The / MeO-2PACz composite hole-selective contact layer has a thickness of 2nm.

[0110] 4. Preparation of perovskite precursor solution: A 1.5 mol / L three-dimensional perovskite precursor solution was prepared. The perovskite composition was: Cs 0.05 (MA 0.10 FA 0.90 ) 0.95 Pb(I 0.90 Br 0.10 3. Weigh PbI2, FAI, MABr, PbBr2 and CsI according to the above stoichiometric ratio, and dissolve them in a DMF / DMSO mixed solvent with a volume ratio of DMF to DMSO of 4:1 to obtain a uniform and transparent perovskite precursor solution.

[0111] 5. Contains Cs x WO 3-δ Preparation of the perovskite absorber layer for DMOAP: The prepared ITO / NiO X The / MeO-2PACz substrate was transferred to a nitrogen glove box, and 50 μL of perovskite precursor solution was dropped onto NiO. X The substrate was coated with a 0.25 mg / mL DMOAP-functionalized Cs solution at 6000 rpm for 45 seconds. 20 seconds after spin-coating began, 150 μL of the solution was applied to the surface of the 0.25 mg / mL DMOAP-functionalized Cs solution. x WO 3-δ An ethyl acetate antisolvent dispersion was dropwise added to the surface of a rotating perovskite wet film. The film was then annealed at 100°C for 15 min to form a Cs-containing film. x WO 3-δ -DMOAP perovskite absorber layer with a thickness of 300nm.

[0112] 6. Preparation of passivation layer on BDAI2: BDAI2 was dissolved in a mixed solvent of IPA / DMSO at a volume ratio of 200:1 to prepare a BDAI2 solution with a concentration of 1 mg / mL. This solution was then spin-coated onto the surface of a perovskite film at 1800 rpm for 30 s. Subsequently, it was annealed at 100°C for 5 min to form an upper passivation layer with a thickness of 5 nm.

[0113] 7. PC61 Fabrication of the BM electron transport layer: PC at a concentration of 20 mg / mL 61 BM chlorobenzene solution was spin-coated onto the passivation layer surface of BDAI2 after BDAI2 treatment. The spin-coating conditions were 1800 rpm and 30 s, forming an electron transport layer with a thickness of 20 nm.

[0114] 8. Preparation of the BCP buffer layer: A 0.5 mg / mL BCP isopropanol solution was spin-coated onto PC. 61 The surface of the BM layer was spin-coated at 6000 rpm for 30 s to form a BCP buffer layer with a thickness of 5 nm.

[0115] 9. Preparation of Ag electrode: The sample was placed in a vacuum evaporation equipment, and an Ag electrode was thermally evaporated under vacuum conditions. The thickness of the Ag electrode was 100 nm, thus obtaining a perovskite solar cell.

[0116] Comparative Example 1

[0117] The only difference from Example 1 is that Cs was not added. x WO 3-δ -DMOAP nanostructures, using only pure ethyl acetate as the antisolvent, yielded a device structure of ITO / NiO. X / MeO-2PACz / Perovskite Absorber Layer / Top Passivation Layer / PC 61 BM / BCP / Ag.

[0118] Experimental Example 1

[0119] The Cs prepared in Example 1 x WO 3-δ Transmission electron microscopy analysis of the -DMOAP nanostructure was performed; results are shown in [link to results]. Figure 2 , Figure 2 Cs as described in Embodiment 1 of this application x WO 3-δ - Transmission electron micrographs of DMOAP, in which Figure 2 In this application, 'a' refers to Cs as described in Embodiment 1. x WO 3-δ - High-magnification transmission electron microscopy image from DMOAP. Figure 2 b in this application refers to Cs as described in Embodiment 1. x WO 3-δ -Low-magnification transmission electron microscopy image from DMOAP.

[0120] Depend on Figure 2 From b, we can see that the obtained Cs x WO 3-δ-DMOAP nanostructures exhibit triangular or near-triangular morphology, with relatively uniform dispersion among particles and no obvious large-area aggregation observed; furthermore, the size of the nanotriangles is approximately 15 nm, classifying them as nanoscale optical enhancement structures. Meanwhile, from Figure 2 From a, we can know that Cs x WO 3-δ The presence of lattice fringes within the -DMOAP nanotriangles indicates a certain degree of crystallinity; the triangular configuration has well-defined edges and sharp corners, providing a structural basis for local electromagnetic field enhancement and multidirectional scattering.

[0121] Experimental Example 2

[0122] The Cs prepared in Example 1 x WO 3-δ -DMOAP was used for scattering spectroscopy analysis, and the results are shown in [link to results]. Figure 3 , Figure 3 Cs as described in Embodiment 1 of this application x WO 3-δ -DMOAP scattering spectrum and perovskite absorption spectrum. Figure 3 It can be seen that Cs x WO 3-δ The -DMOAP dispersion exhibits a broad spectral scattering response in the 400 nm–750 nm range, which matches well with the main absorption region of the perovskite absorption layer. This result indicates that Cs x WO 3-δ -DMOAP nanotriangles can enhance the scattering of incident light within the effective absorption band of perovskite. When introduced into the perovskite absorption layer, they can cause some incident light to propagate in multiple directions, extending the effective propagation path of light within the perovskite layer and thus increasing the probability of photons being absorbed by the perovskite.

[0123] Experimental Example 3

[0124] Figure 4 Cs as described in Embodiment 1 of this application x WO 3-δ - A schematic diagram of omnidirectional scattering by DMOAP and its optical field simulation results in the perovskite absorption layer, wherein Figure 4 In this application, 'a' refers to Cs as described in Embodiment 1. x WO 3-δ -DMOAP omnidirectional scattering diagram Figure 4 b in this application refers to Cs as described in Embodiment 1. x WO 3-δ -DMOAP optical field simulation results in perovskite absorption layer.

[0125] Depend on Figure 4 From a, we can see that the triangular configuration Cs x WO3-δ -DMOAP has multiple edges and sharp corners, allowing incident light to be scattered in multiple directions around the nanostructure, forming an omnidirectional light distribution approximating Lambertian scattering. Figure 4 As can be seen from a, the light field simulation results show that when Cs x WO 3-δ When the -DMOAP nanotriangle is located within the perovskite absorption layer, the electromagnetic field surrounding the nanostructure undergoes a significant change. The Poynting vector, indicated by the red line in the figure, shows that incident light is deflected, scattered, and redistributed near the nanotriangle, transforming light energy that originally propagated primarily along the incident direction into multi-directional propagation. This light field modulation effect can lengthen the propagation path of light within the perovskite absorption layer, improving the utilization efficiency of the perovskite layer for incident light, especially obliquely incident light.

[0126] Test Example 4

[0127] Figure 5 Cs as described in Embodiment 1 of this application x WO 3-δ -A schematic diagram illustrating the enhancement mechanism of DMOAP in perovskite solar cells, where Figure 5 In this application, 'a' refers to Cs as described in Embodiment 1. x WO 3-δ -DMOAP localized surface plasmon effect in perovskite solar cells Figure 5 b in this application refers to Cs as described in Embodiment 1. x WO 3-δ - DMOAP's omnidirectional scattering effect in perovskite solar cells Figure 5 c in this application refers to Cs as described in Embodiment 1 of this application. x WO 3-δ -DMOAP enhances charge extraction in perovskite solar cells.

[0128] Depend on Figure 5 From a, we can know that Cs x WO 3-δ Cs doping and oxygen vacancies in -DMOAP can tune its free carrier concentration, resulting in localized surface plasmon-related optical enhancement effects. When Cs x WO 3-δ When -DMOAP is distributed in the perovskite absorption layer, it can form an enhanced local optical field around the nanostructure, thereby improving the local light absorption and photogenerated carrier generation rate of the perovskite.

[0129] Depend on Figure 5 From b, we can see that the triangular configuration Cs x WO 3-δ-DMOAP features edges, sharp corners, and multi-directional geometric boundaries, which can induce all-directional scattering of incident light. This scattering effect can extend the effective propagation path of light in the perovskite absorption layer, which is particularly beneficial for improving the absorption capability of the device under non-perpendicular incident light conditions.

[0130] Depend on Figure 5 As can be seen from c, Cs after surface functionalization x WO 3-δ -DMOAP nanotriangles can be well dispersed in the perovskite absorber layer, and their Poynting vector can cover the transport layer region. They may improve the carrier separation, transport and extraction process in local areas, reduce local recombination loss, and thus promote charge extraction.

[0131] The three effects mentioned above work together to make Cs-containing x WO 3-δ -DMOAP's perovskite devices show improvements in current output, photoelectric conversion efficiency, and response to large-angle incident light.

[0132] Experimental Example 5

[0133] Figure 6 For the perovskite solar cells described in Comparative Examples 1 and 2 of this application under different incident angle illumination conditions J - V curve, in which Figure 6 In Figure 'a', the perovskite solar cell described in Comparative Example 1 of this application is illuminated under different incident angles. J - V curve, Figure 6 In Figure 2, b represents the perovskite solar cell described in Example 2 of this application under different incident angle illumination conditions. J - V curve.

[0134] For specific photovoltaic parameter data, please refer to Tables 1 and 2. Table 1 shows the photovoltaic performance parameters corresponding to Comparative Example 1, and Table 2 shows the photovoltaic performance parameters corresponding to Example 2.

[0135] Table 1. Photovoltaic parameters of Comparative Example 1 under different incident light angles.

[0136] Table 2 Photovoltaic parameters under different incident light angles in Example 2

[0137] As shown in Tables 1 and 2, under a 0° incident angle, the device in Example 2 exhibits higher short-circuit current density and photoelectric conversion efficiency compared to Comparative Example 1, indicating that Cs x WO 3-δThe introduction of -DMOAP nanotriangles can enhance the photocurrent output of the perovskite absorber layer under perpendicular incident light conditions. This result is consistent with Cs x WO 3-δ -DMOAP’s localized surface plasmon enhancement effect is consistent with its charge extraction enhancement effect.

[0138] Within the incident angle range of 10° to 60°, both the current and efficiency of the devices in Comparative Example 1 and Example 2 decreased with increasing incident angle. However, compared to Comparative Example 1, the device in Example 2 exhibited a smaller performance degradation, demonstrating higher short-circuit current retention and efficiency retention. This result indicates that the triangular configuration Cs x WO 3-δ - The omnidirectional scattering effect of DMOAP can improve the utilization of oblique incident light by perovskite devices, enabling the devices to maintain good photovoltaic output even under large-angle incident light conditions.

[0139] comprehensive Figures 1-6 As shown in Tables 1 and 2, this application prepared Cs with a size of approximately 15 nm, uniform dispersion, and triangular configuration by hot injection molding and surface functionalization treatment. x WO 3-δ -DMOAP nanostructure. This nanostructure can be stably dispersed in ethyl acetate antisolvent and enters the perovskite absorber layer through an antisolvent dropwise addition process.

[0140] Scattering spectra indicate that Cs x WO 3-δ -DMOAP nanotriangles exhibit a broad spectral scattering response in the 400nm–750nm range, matching the main absorption range of perovskites. Optical field simulations further illustrate that Cs x WO 3-δ -DMOAP nanotriangles can induce localized optical field enhancement, Poynting vector deflection, and redistribution of light energy flow in the perovskite layer, thereby improving the effective utilization of light in the perovskite absorption layer.

[0141] Device testing results show that, under a 0° incident angle, Cs-containing x WO 3-δ -DMOAP devices exhibit higher short-circuit current density and photoelectric conversion efficiency, demonstrating the effectiveness of LSPR-related localized optical field enhancement and charge extraction enhancement effects; under incident angles of 10°–60°, Cs-containing devices... x WO 3-δ -DMOAP devices exhibit less performance degradation, demonstrating the superior performance of the triangular Cs configuration. x WO 3-δ - The omnidirectional scattering effect of DMOAP can improve the large-angle incident light response of perovskite solar cells.

[0142] Therefore, the Cs described in this application x WO 3-δ -DMOAP nanotriangles can achieve synergistic gains through the LSPR effect, omnidirectional scattering effect, and charge extraction enhancement effect, thereby improving the light utilization efficiency and angle adaptability of perovskite solar cells without changing the structure of the main device.

[0143] The above description is merely a preferred embodiment of this application, but the scope of protection of this application is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in this application, based on the technical solution and inventive concept of this application, should be included within the scope of protection of this application.

Claims

1. A method for preparing cesium-doped tungsten oxide, characterized in that, Includes the following steps: a) Mix the cesium source, organic acid, and first organic phase to obtain the first solution; b) Mix the tungsten source, trioctylphosphine oxygen, and the second organic phase to obtain a second solution; c) React the first and second solutions to obtain cesium-doped tungsten oxide; The cesium-doped tungsten oxide has the chemical formula of formula (I): Cs x WO 3-δ Formula (I); where 0.01≤δ≤0.5, 0.3≤x≤1.2; the cesium-doped tungsten oxide is triangular nanocrystals.

2. The preparation method according to claim 1, characterized in that, In step b), the molar ratio of tungsten to trioctylphosphine oxygen in the tungsten source is 1:(0.2~10).

3. The preparation method according to claim 1, characterized in that, In step c), the molar ratio of cesium in the first solution to tungsten in the second solution is (0.3~1.2):1; The reaction temperature is 260°C to 330°C, and the time is 0.5 min to 60 min.

4. A method for preparing functionalized cesium-doped tungsten oxide, characterized in that, Includes the following steps: Cesium-doped tungsten oxide was reacted with an organosilane coupling agent to obtain functionalized cesium-doped tungsten oxide; The method for preparing the cesium-doped tungsten oxide is the method described in any one of claims 1 to 3.

5. A method for fabricating a perovskite solar cell, characterized in that, Includes the following steps: A hole transport layer is formed on the substrate surface; A perovskite absorption layer containing plasmonic nanostructures is formed on the surface of the hole transport layer; An upper passivation layer is formed on the surface of the perovskite absorber layer containing plasmon nanostructures; An electron transport layer is formed on the surface of the upper passivation layer; An electrode layer is formed on the surface of the electron transport layer; The plasmonic nanostructure is selected from cesium-doped tungsten oxide or functionalized cesium-doped tungsten oxide; The method for preparing the cesium-doped tungsten oxide is the method described in any one of claims 1 to 3; The method for preparing the functionalized cesium-doped tungsten oxide is the method described in claim 4.

6. The preparation method according to claim 5, characterized in that, The mass fraction of plasmonic nanostructures in the perovskite absorber layer containing plasmonic nanostructures is 0.01wt%~0.2wt%.